Long‐term efficacy and safety of sonidegib in patients with locally advanced and metastatic basal cell carcinoma: 30‐month analysis of the randomized phase 2 BOLT study. (6th November 2017) - Lear, J.T.; Migden, M.R.; Lewis, K.D.; Chang, A.L.S.; Guminski, A.; Gutzmer, R.; Dirix, L.; Combemale, P.; Stratigos, A.; Plummer, R.; Castro, H.; Yi, T.; et al.
Abstract: Background: Patients with locally advanced basal cell carcinoma (laBCC) or metastatic BCC (mBCC), two difficult‐to‐treat populations, have had limited treatment options. Sonidegib, a hedgehog pathway inhibitor (HPI), was approved in laBCC based on results from the BOLT trial. Objective: To evaluate long‐term efficacy and safety of sonidegib in laBCC and mBCC in the BOLT 18‐ and 30‐month analyses. Methods: BOLT (NCT01327053, ClinicalTrials.gov), a double‐blind phase 2 study, enrolled patients from July 2011 until January 2013. Eligible HPI‐treatment–naïve patients with laBCC not amenable to curative surgery/radiotherapy or mBCC were randomized 1 : 2 to sonidegib 200 mg (laBCC, n  = 66; mBCC, n  = 13) or 800 mg (laBCC, n  = 128; mBCC, n  = 23). Tumour response was assessed per central and investigator review. Results: With 30 months of follow‐up, among patients treated with sonidegib 200 mg (approved dose), objective response rates were 56.1% (central) and 71.2% (investigator) in laBCC and 7.7% (central) and 23.1% (investigator) in mBCC. Tumour responses were durable as follows: median duration of response was 26.1 months (central) and 15.7 months (investigator) in laBCC and 24.0 months (central) and 18.1 months (investigator) in mBCC. Five patients with laBCC and three with mBCC in the 200‐mg arm died. Median overall survival was not reached in either population; 2‐year overall survival rates were 93.2% (laBCC) and 69.3% (mBCC). In laBCC, efficacy was similar regardless of aggressive or non‐aggressive histology. Sonidegib 200 mg continued to have a better safety profile than 800 mg, with lower rates of grade 3/4 adverse events (43.0% vs. 64.0%) and adverse events leading to discontinuation (30.4% vs. 40.0%). Conclusion: Sonidegib continued to demonstrate long‐term efficacy and safety in these populations. These data support the use of sonidegib 200 mg per local treatment guidelines.